Birth of a Live Cria After Transfer of a Vitrified-Warmed Alpaca (Vicugna pacos) Preimplantation Embryo - Lutz, Jennifer C.; Johnson, Susan L.; Duprey, Kimberly J.; Taylor, Paul J.; Vivanco-Mackie, Henry William; Ponce-Salazar, Daniel; Miguel-Gonzales, Marlene; Youngs, Curtis R. (Frontiers in Veterinary Science, 2020)
The alpaca (Vicugna pacos) is an important species for the production of fiber and food. Genetic improvement programs for alpacas have been hindered, however, by the lack of field-practical techniques for artificial insemination and embryo transfer. In particular, successful techniques for the cryopreservation of alpaca preimplantation embryos have not been reported previously. The objective of this study was to develop a field-practical and efficacious technique for cryopreservation of alpaca preimplantation embryos using a modification of a vitrification protocol originally devised for horses and adapted for dromedary camels. Four naturally cycling non-superovulated Huacaya females serving as embryo donors were mated to males of proven fertility. Donors received 30 μg of gonadorelin at the time of breeding, and embryos were non-surgically recovered 7 days after mating. Recovered embryos (n = 4) were placed individually through a series of three vitrification solutions at 20°C (VS1: 1.4 M glycerol; VS2: 1.4 M glycerol + 3.6 M ethylene glycol; VS3: 3.4 M glycerol + 4.6 M ethylene glycol) before loading into an open-pulled straw (OPS) and plunging directly into liquid nitrogen for storage. At warming, each individual embryo was sequentially placed through warming solutions (WS1: 0.5 M galactose at 37°C; WS2: 0.25 M galactose at 20°C), and warmed embryos were incubated at 37°C in 5% CO2 in humidified air for 20–22 h in 1 ml Syngro® holding medium supplemented with 10% (v/v) alpaca serum to perform an initial in vitro assessment of post-warming viability. Embryos whose diameter increased during culture (n = 2) were transferred individually into synchronous recipients, whereas embryos that did not grow (n = 2) were transferred together into a single recipient to perform an in vivo assessment of post-warming viability. Initial pregnancy detection was performed ultrasonographically 29 days post-transfer when fetal heartbeat could be detected, and one of three recipients was pregnant (25% embryo survival rate). On November 13, 2019, the one pregnant recipient delivered what is believed to be the world's first cria produced from a vitrified-warmed alpaca embryo.